Cover Image. Issue 2 (11th February 2023) - Kon, Risako; Ikarashi, Nobutomo; Onuma, Kazuhiro; Yasukawa, Zenta; Ozeki, Makoto; Sakai, Hiroyasu; Kamei, Junzo
Abstract : The cover image is based on the Original Article Effect of partially hydrolyzed guar gum on the expression of aquaporin‐3 in the colon by Risako Kon et al., https://doi.org/10.1002/fsn3.3150